2022
DOI: 10.3991/ijet.v17i14.32809
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis Method for Training of College Students’ Entrepreneurial Resilience from the Perspective of Entrepreneurial Ecological Environment

Abstract: Due to the constraints of the entrepreneurial ecological environment and the heterogeneity of the individual college students and their interpersonal relationships and situations, some specific problems like psychological potential development and stress buffering effect in the process of college students’ entrepreneurial resilience cultivation have not been fundamentally resolved. Therefore, this paper explores the qualitative analysis method for cultivation of college students’ entrepreneurial resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Among the identified gaps, Li et al (2022) found a scarcity of longitudinal research analyzing prolonged crises. Finally, Pita & Costa (2021) propose incorporating intersectional perspectives in future studies to consider the diversity of experiences among female entrepreneurs.…”
Section: Gaps and Future Researchmentioning
confidence: 99%
“…Among the identified gaps, Li et al (2022) found a scarcity of longitudinal research analyzing prolonged crises. Finally, Pita & Costa (2021) propose incorporating intersectional perspectives in future studies to consider the diversity of experiences among female entrepreneurs.…”
Section: Gaps and Future Researchmentioning
confidence: 99%